CD107a+ (LAMP-1) Cytotoxic CD8+ T-Cells in Lupus Nephritis Patients - Wiechmann, Anika; Wilde, Benjamin; Tyczynski, Bartosz; Amann, Kerstin; Abdulahad, Wayel H.; Kribben, Andreas; Lang, Karl Sebastian; Witzke, Oliver; Dolff, Sebastian (Frontiers in Medicine, 2021)
Cytotoxic CD8+ T-cells play a pivotal role in the pathogenesis of systemic lupus erythematosus (SLE). The aim of this study was to investigate the role of CD107a (LAMP-1) on cytotoxic CD8+ T-cells in SLE-patients in particular with lupus nephritis. Peripheral blood of SLE-patients (n=31) and healthy controls (n=21) was analyzed for the expression of CD314 and CD107a by flow cytometry. Kidney biopsies of lupus nephritis patients were investigated for the presence of CD8+ and C107a+ cells by immunohistochemistry. The percentages of CD107a+ on CD8+ T-cells were significantly decreased in SLE-patients as compared to healthy controls (40.2 ±18.5 % vs. 47.9 ± 15.0 %, p=0.02). This was even more significant in SLE-patients with inactive disease. There was a significant correlation between the percentages of CD107a+CD8+ T-cells and SLEDAI. The evaluation of lupus nephritis biopsies showed a significant number of CD107a+CD8+ T-cells mainly located in the peritubular infiltrates. The intrarenal expression of CD107a+ was significantly correlated with proteinuria. These results demonstrate that CD8+ T-cells of patients with systemic lupus erythematosus have an altered expression of CD107a which seems to be associated with disease activity. The proof of intrarenal CD107a+CD8+ suggests a role in the pathogenesis of lupus nephritis.